Effectiveness of Concrete Crack Repair Using Bacillus subtilis and Calcium Lactate - Rahmawan, Rama Zaky; Erizal, Erizal; Putra, Heriansyah; Oktafiani, Pradyta Galuh; Sutoyo, Sutoyo (Universitas Negeri Yogyakarta, 2025)
Cracks facilitate aggressive substances entering the steel easily and cause corrosion of the reinforcement. There are several innovative methods for dealing with cracks in concrete, one of which is using bacteria. The purpose of using bacteria and CaL is to find out the role and effectiveness of repairing cracks in concrete. In outline, several methods and tests are carried out, including bacterial culture, test tube, concrete sample making, concrete curing, compressive strength testing, permeability testing, absorption testing, image processing testing, and microscopic testing. The test tube results showed that the highest mass of calcite was found in a solution of 2 ml of bacteria and CaL with a concentration of 65.4 g/L. The cracks appeared closed visually at 28 days of age. Through imageJ software, the crack repair rate in concrete reaches 95.94%. The effect of adding B. subtilis and CaL was proven to be able to close concrete cracks and increase the compressive strength of cracked concrete by 13.16%, reduce permeability by 53.12%, and absorption by 22.20%. This was confirmed by SEM testing and VHX-7000 observations which showed the presence of calcite crystals in the concrete pores and filled the concrete crack areas. This study elucidated that using bacillus subtilis bacteria and calcium Lactate in self-healing concrete is an effective technique to repair the concrete crack.